Ответ:
2. 2
3. 4
4. 2
5. 3
6. 2
Пошаговое объяснение:
Что увижу, то напишу)
2. 2
(а - 3)(b - 5)
a*b + a*(- 5) + (- 3)*b + (- 3)*(- 5)
ab - 5a - 3b + 15
В данном случае от перестановки -5а и -3b ничего не будет, поэтому
ab - 3b - 5a + 15.
3. 4
![4 {a}^{2} - 20a + 25 \\ {(2a - 5)}^{2} 4 {a}^{2} - 20a + 25 \\ {(2a - 5)}^{2}](https://tex.z-dn.net/?f=%204%20%7Ba%7D%5E%7B2%7D%20-%2020a%20%2B%2025%20%5C%5C%20%7B%282a%20-%205%29%7D%5E%7B2%7D%20)
4. 2
![\frac{6b - 18}{ {b}^{2} - 9} = \frac{6(b - 3)}{(b + 3)(b - 3)} = \frac{6}{b + 3} \frac{6b - 18}{ {b}^{2} - 9} = \frac{6(b - 3)}{(b + 3)(b - 3)} = \frac{6}{b + 3}](https://tex.z-dn.net/?f=%20%5Cfrac%7B6b%20-%2018%7D%7B%20%7Bb%7D%5E%7B2%7D%20%20-%209%7D%20%20%3D%20%20%5Cfrac%7B6%28b%20-%203%29%7D%7B%28b%20%2B%203%29%28b%20-%203%29%7D%20%20%3D%20%20%5Cfrac%7B6%7D%7Bb%20%2B%203%7D%20)
5. 3
![{2x}^{2} + 12x + 18 \\ 2 {(x + 3)}^{2} {2x}^{2} + 12x + 18 \\ 2 {(x + 3)}^{2}](https://tex.z-dn.net/?f=%20%7B2x%7D%5E%7B2%7D%20%2B%2012x%20%2B%2018%20%5C%5C%202%20%7B%28x%20%2B%203%29%7D%5E%7B2%7D%20)
6. 2
![5 {y}^{3} - 5y = 0 \\ 5y( {y}^{2} - 1) = 0 \\ 5y = 0 \\y = 0 \\ \\ {y}^{2} - 1 = 0 \\ y = 1 5 {y}^{3} - 5y = 0 \\ 5y( {y}^{2} - 1) = 0 \\ 5y = 0 \\y = 0 \\ \\ {y}^{2} - 1 = 0 \\ y = 1](https://tex.z-dn.net/?f=5%20%7By%7D%5E%7B3%7D%20%20-%205y%20%3D%200%20%20%5C%5C%205y%28%20%20%7By%7D%5E%7B2%7D%20%20-%201%29%20%3D%200%20%5C%5C%205y%20%20%20%3D%200%20%5C%5Cy%20%3D%200%20%5C%5C%20%20%5C%5C%20%20%7By%7D%5E%7B2%7D%20%20-%201%20%3D%200%20%5C%5C%20y%20%3D%201)